Comparison of culturable antibiotic-resistant bacteria in polluted and non-polluted air in Beijing, China - Mao, Yixin (Environ Int, 2019)
BACKGROUND: Air pollution has been a serious health issue in Beijing for years. Airborne antibiotic-resistant bacteria could be a potential health crisis as reserve of antibiotic resistance transmission in environment. The composition and antibiotic resistance pattern of culturable bacterial community and how these are affected by air pollution remain unclear. OBJECTIVES: This study aimed to compare the compositions and antibiotic resistance patterns of culturable bacteria in polluted and non-polluted weather conditions in Beijing. METHODS: Air samples were collected indoors and outdoors during polluted and non-polluted weather using six-stage Andersen Samplers. For each isolated bacterium, the 16S ribosomal RNA gene was amplified, sequenced, and blasted against the National Center for Biotechnology Information database Antibiotic resistance was conducted by antimicrobial susceptibility testing. RESULTS: Bacterial concentration in polluted weather was significantly higher than in non-polluted weather, both indoors and outdoors (P < 0.05). Gram-positive bacteria (GPB) were dominant in both weathers but gram-negative bacteria (GNB) were more abundant in polluted weather than non-polluted weather both indoors and outdoors. Multidrug-resistant (MDR) bacteria occupied 23.7% of all bacterial isolates, 22.4% of isolates from polluted weather and 27.8% of isolates from non-polluted weather. Penicillins were resisted by 72.4% and 83.3% of isolates from polluted and non-polluted weather, respectively. CONCLUSIONS: The bacterial concentration was significantly higher in polluted weather, compared to non-polluted weather. Polluted weather is correlated with changes in the bacterial composition in the air, with a greater abundance of GNB. Penicillins was resisted by over 70% of bacterial isolates. The abundance of MDR bacteria suggested potential risks for human health.